A planning framework based on system theory and GIS for urban emergency shelter system: A case of Guangzhou, China. Issue 3 (3rd April 2017) - Chen, Wei; Zhai, Guofang; Fan, Chenjing; Jin, Wenbo; Xie, Ying
ABSTRACT: The urban emergency shelter is of great significance to disaster prevention and mitigation. In China, the demand is enormous for emergency shelters while their construction generally lags behind the economic and social development, which has resulted in heavy casualties and economic losses. This article considers emergency shelters as a complete system from systemic perspective and also proposes a planning framework for emergency shelter system, including the function, hierarchy, type, scale, layout, standard, and supporting-service system of the shelters. Then, an empirical study applying the framework in GIS platform in the urban emergency shelter planning of Guangzhou city was conducted and highly valued by local experts and citizens as a feasible scheme to guide the construction of emergency shelters, indicating that the framework is an appropriate tool for urban emergency shelter planning.